2018
DOI: 10.5688/ajpe6245
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Student Knowledge Through a Comprehensive Oncology Simulation

Abstract: To evaluate the impact of a comprehensive oncology simulation on pharmacy students' knowledge and perceptions related to oncology pharmacy practice. Third-year pharmacy students at the University of South Florida completed an ovarian cancer case-based simulation. Stations involved patient-specific order set completion, counseling, order verification, and aseptic technique. Pre- and post-simulation assessments regarding therapeutic knowledge and aseptic technique as well as perceptions of pharmacists' roles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 6 publications
1
33
1
Order By: Relevance
“…To our knowledge, no previous studies have evaluated the impact of simulated rounds on changes in sepsis knowledge. Although previous studies have indicated that simulation exercises increase knowledge and skills, [9][10][11][12][17][18][19][20] our students did not show a statistically significant change in sepsis knowledge between the didactic lecture and simulation. This finding may be due to significant changes already being observed between the pre-and post-didactic lecture surveys as well as small sample sizes.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…To our knowledge, no previous studies have evaluated the impact of simulated rounds on changes in sepsis knowledge. Although previous studies have indicated that simulation exercises increase knowledge and skills, [9][10][11][12][17][18][19][20] our students did not show a statistically significant change in sepsis knowledge between the didactic lecture and simulation. This finding may be due to significant changes already being observed between the pre-and post-didactic lecture surveys as well as small sample sizes.…”
Section: Discussioncontrasting
confidence: 94%
“…Student teams who had previous simulation training demonstrated increased knowledge and skills over teams without previous training for 75% of ACLS skills observed. In 2018, Serag-Bolos et al 10 evaluated the impact of an oncology simulation on the knowledge and perceptions of 109 pharmacy students using a 5-point Likert scale (5 = strongly agree; 1 = strongly disagree). The authors found an increase in student knowledge as well as improvements in perceptions of roles/responsibilities and self-confidence.…”
mentioning
confidence: 99%
“…However, there are few studies evaluating student pharmacists' confidence and perceptions of oncology pharmacy while also assessing knowledge of oncology and oncology pharmacy practice. 6,7 Our study was conducted to explore student pharmacists' confidence in and perceptions of oncology pharmacy before and after completing a four-part interactive activity before the oncology course and a two-hour session in the fourth week of the course. These interventions resulted in significant improvements in scores on several items.…”
Section: Discussionmentioning
confidence: 99%
“…Students worked in preassigned groups, which reinforced their teamwork and communication skills. 7 Students experienced a more realistic environment simulated to represent different practice settings using a four-station activity. 7 The range of oncology questions asked of the students reflected real scenarios that oncology pharmacists are expected to manage and resolve as the scope of their responsibilities expands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation